Effect of pH of In-Office Bleaching Gels and Timing of Fluoride Gel Application on Microhardness and Surface Morphology of Enamel - Fariba Motevasselian; Hamid Kermanshah; Dorara Dortaj; Frank Lippert (Hindawi Limited, 2023)
Objective. To assess microhardness (VH) of enamel treated with two in-office bleaching agents with different pH and to study the effect of post- and prebleaching fluoride therapy. Materials and Methods. Eighty bovine incisors were divided into eight groups: G1-Unbleached group; G2-2% NaF; G3-Pola Office (pH = 3.8); G4-Pola Office+ (pH = 7); G5-Pola Office followed by 2% NaF; G6-2% NaF followed by Pola Office; G7-Pola Office+ followed by 2% NaF; G8-2% NaF followed by Pola Office+. Bleaching was conducted 3x with 1-week intervals (T1/T7/T14). Specimens were kept in artificial saliva. VH was measured at T1, T7, and T14. Data were analyzed using repeated measure ANOVA. Surface morphology was assessed using scanning electron microscopy. Result. There was no significant difference among the groups at T1. No significant difference was found between G3 and G4 at all intervals. 2% NaF (G5/G6 vs. G3) significantly prevented softening at T7 and T14. Some nonsignificant hardening was observed for 2% NaF for G7/G8 vs. G4. At T14, G3 showed the lowest VH values. G5 showed higher VH values compared to other groups apart from G6-G7. No relationship between bleaching protocols and surface morphology was observed. Conclusion. Pola Office caused the most softening. 2% NaF gel application after Pola Office bleaching was effective in recovering enamel hardness. Fluoride application after Pola Office+ bleaching provided little benefit.